Avatar-based models, tools, and innovation in the digital economy - Mkrttchian, Vardan, 1950-; Gamidullaeva, Leyla, 1985-; Aleshina, Ekaterina, 1978- (Business Science Reference, 2020)
"This book examines the use of avatar-based models, tools, and neuro natural platforms in the digital economy"--